Frequency and diversity of phlebotomine sand flies (Diptera: Psychodidae) in Sinop, State of Mato Grosso, Brazil - Sirlei Franck Thies; Roberta Vieira de Morais Bronzoni; Mariano Martinez Espinosa; Cladson de Oliveira Souza; Ana Lucia Maria Ribeiro; Emerson Soares dos Santos; Edelberto Santos Dias; Amílcar Sabino Damazo (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Understanding the diversity of sand flies is important for the epidemiology and control of leishmaniasis. This study aimed to understand the frequency, diversity, and seasonality of medically important sand flies in the municipality of Sinop, State of Mato Grosso, Brazil. METHODS: The study was conducted in an urban area, including four ecotypes with different levels of urbanization. The sand flies were collected using light traps for three nights per month, from May 2014 to April 2015. RESULTS: A total of 62,745 sand flies was collected, 52.34% of which were female. The frequency and diversity of sand flies was the highest in areas of permanent preservation (APPs) (96.85%), and was lower in more urbanized areas. Lutzomyia dasypodogeton was the most frequent species in the APPs. Lutzomyia antunesi was the most frequent in neighborhoods with forest fragments and neighborhoods around APPs, and L. aragaoi was the most frequent in completely urbanized neighborhoods. A higher frequency and diversity of sand flies was observed in the rainy season (87.92%) than in the dry season (12.08%). Eight medically important species were captured, and Lutzomyia antunesi, which is associated with American cutaneous leishmaniasis and visceral leishmaniasis, was observed in all ecotypes throughout the year. CONCLUSIONS: We observed a high frequency and diversity of sand flies in all urban areas, and some species collected were major vectors of leishmaniasis. These results support the need for further studies of the natural rates of infection of these insects and the circulation of the disease in hosts and vectors.